Intrahousehold impact of the transfer of modern agricultural technology: a gender perspective - Naved, Ruchira T. (International Food Policy Research Institute, 2000)
This study explores the intrahousehold impact of transfer of modern agricultural technology from a gender perspective. The data suggest that group-based programs targeting women have a greater potential to address gender relations within the household and society than do programs targeting women as individuals. In male-dominated societies where women have limited access to internal or external support networks, programs targeting women as individuals that do not also provide alternative sources of support are bound to fail in their gender goals.